2012
DOI: 10.1371/journal.pone.0031420
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and Cellular CMV Responses in Healthy Donors; Identification of a Frequent Population of CMV-Specific, CD4+ T Cells in Seronegative Donors

Abstract: CMV status is an important risk factor in immune compromised patients. In hematopoeitic cell transplantations (HCT), both donor and recipient are tested routinely for CMV status by serological assays; however, one might argue that it might also be of relevance to examine CMV status by cellular (i.e., T lymphocyte) assays. Here, we have analyzed the CMV status of 100 healthy blood bank donors using both serology and cellular assays. About half (56%) were found to be CMV seropositive, and they all mounted strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 43 publications
2
23
1
Order By: Relevance
“…Additionally, as recently shown, CMV-seronegative individuals can have CMVresponsive T-cells thereby suggesting a former encounter with CMV, and this might also have affected our analyses. 23,24 Finally, our study is the first to show an association between CMV infection and HZ, further causal relations should be studied in other studies.…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, as recently shown, CMV-seronegative individuals can have CMVresponsive T-cells thereby suggesting a former encounter with CMV, and this might also have affected our analyses. 23,24 Finally, our study is the first to show an association between CMV infection and HZ, further causal relations should be studied in other studies.…”
Section: Discussionmentioning
confidence: 62%
“…as transplant patients and pregnant women, was recently already shown for CMV (66) and had already been shown for various pathogens, such as hepatitis C virus (67). CMV pp65-specific IFN-␥-producing T cells were more frequent than those against VZV IE63, VZV gE, TT, and AdV penton.…”
Section: Fig 4 Comparing Ifn-␥-producing T-cell Percentages (Of Cd3mentioning
confidence: 62%
“…CMV‐specific T cells have been previously reported in CMV‐IgG seronegative individuals. Loeth et al [] detected CMV pp65‐reactive Th cells in healthy CMV‐seronegative blood bank donors and Lúcia et al [] showed CMV‐sensitized individuals with protective CMV‐specific memory T and B cells among seronegative kidney transplant recipients. These T cells may have been induced by previous exposure to CMV which was sufficient to activate T cells but failed to mount an humoral immune response.…”
Section: Discussionmentioning
confidence: 99%